1/2(3а-8)-1/3(2b+9) = 6,6
0,5*3a-0,5*8 - 0,3*2b+0,3*9 = 1,5a-4 - 0,6b+2,7
1,5a-4-0,6b+2,7 = 1,5a-4+2,7-0,6b = 1,5a-1,3-0,6b
Выражение 1,5a-1,3-0,6b при a = , b =
1,5*-1,3-0,6* =
1)
2) 8-1,3 = 6,7
3)
4) 6,7-0,1 = 6,6
ответ: 6,6.
1/2(3а-8)-1/3(2b+9) = 6,6
0,5*3a-0,5*8 - 0,3*2b+0,3*9 = 1,5a-4 - 0,6b+2,7
1,5a-4-0,6b+2,7 = 1,5a-4+2,7-0,6b = 1,5a-1,3-0,6b
Выражение 1,5a-1,3-0,6b при a =
, b = ![\frac{1}{6}](/tpl/images/0977/8073/c8870.png)
1,5*
-1,3-0,6*
=
1)![\frac{3}{2} * \frac{16}{3} = \frac{8}{1} = 8](/tpl/images/0977/8073/d3a58.png)
2) 8-1,3 = 6,7
3)![\frac{6}{10} * \frac{1}{6} = \frac{1}{10} = 0,1](/tpl/images/0977/8073/28147.png)
4) 6,7-0,1 = 6,6
ответ: 6,6.